Collaboration between subject teachers and special education teachers in Finnish lower secondary schools - Ninnu Kotilainen; Riikka Sirkko; Marjatta Takala (Education Inquiry)
It has been argued that successful teacher collaboration is challenging to implement in a secondary school context, where teaching is based on subjects. However, collaboration between subject teachers and special education teachers (SETs) is important, especially in promoting inclusion. This is why we wanted to determine what is included in their collaboration in Finnish secondary schools, and how teachers describe this collaboration. Together, 175 subject teachers and SETs responded to questions about collaboration. Using content analysis, we found that collaboration usually means exchanging information on students or an upcoming lesson. Other, deeper forms of collaboration, such as co-teaching or joint planning exist but are much rarer due to inflexible school structures and lack of time. Four categories describing teacher collaboration were found. These categories of dysfunctional, uncertain, comfortable and professional collaboration were compared to Hargreaves’ ideas of individualistic and collaborative teacher cultures. No school-wide teacher culture was detected, suggesting that individual teachers’ collaborative skills and willingness to collaborate are a factor in the success of collaboration.